Indonesian primary care physicians profile in 2011: did practicing hours and conversion program for family medicine differentiate their services and continuing medical education activities? - Widyahening, Indah S; Thuraiappah, Daniel M; Tin, Myo Han; Vidiawati, Dhanasari (BioMed Central The Open Access Publisher, 2014)
Background: In Indonesia, Family Medicine as a discipline is being developed through short courses since 12 years ago. A conversion program to become Family Physicians has been introduced recently. Among the 70,000 primary care physicians there are variety of practitioners, from new interns who start general practice to senior general practitioners. This study aims to describe the current Indonesian Primary Care Physicians (PCPs) profile which includes services provided and facilities as well as comparing the profile according to participation in the conversion program and practice hours. Methods: A survey was carried out by using pre-tested, semi-structured and self-administered questionnaire among Indonesian primary care physicians (PCPs) who attended ASEAN Regional Primary Care Conference in Jakarta, November 2011. The survey elicited information regarding their practice environment, services provided, equipment,investigations provided, procedures, facilities and continuing medical education (CME)activities. Results: Out of 240 PCPs participated, 65.4% (157/240) of them were family physicians and 67.1% (161/240) of them were full time practitioners (practice > 30 hours per week). Services like body mass index (BMI) measurement, substance abuse program, respiratory function test, mental health assessment, and cardiovascular assessment were provided by less than 50% of the PCPs as well as some investigations like electrocardiograph (ECG), proctoscopy, ultrasound, visual examination and funduscopy. Family Physicians significantly provided more house call services (77% vs 63%; p = 0.01), than those who are not. No other significant difference was found in the practice of the family physicians compare to non-family physicians. Conclusions: The Indonesian PCPs were lacking in the provision of some particular medical procedures, management and follows up of acute and chronic conditions, and preventive medicine and health education. Improvement of primary health care has been seen globally as necessary effort in health systems reform and this information could provide guidance toward the efforts to improve the quality of primary care physicians in Indonesia.